2017
DOI: 10.1038/s41598-017-12814-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between crystallographic anisotropy and dendritic orientation selection of binary magnesium alloys

Abstract: Both synchrotron X-ray tomography and EBSD characterization revealed that the preferred growth directions of magnesium alloy dendrite change as the type and amount of solute elements. Such growth behavior was further investigated by evaluating the orientation-dependent surface energy and the subsequent crystallographic anisotropy via ab-initio calculations based on density functional theory and hcp lattice structure. It was found that for most binary magnesium alloys, the preferred growth direction of the α-Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…34,35 It has been confirmed that the position of additional atoms does not affect significantly the variation trend of the calculated surface energy with respect to the surface orientations. 36,37 The concentration of the additional elements for the magnesium alloys was chosen on the basis of their solubility in the solid or the maximum solute concentration in the Mg matrix. 36 We optimized the atomic structure of bulk materials and then constructed the surface slab model with respect to the growth orientations of the α-Mg dendrite.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…34,35 It has been confirmed that the position of additional atoms does not affect significantly the variation trend of the calculated surface energy with respect to the surface orientations. 36,37 The concentration of the additional elements for the magnesium alloys was chosen on the basis of their solubility in the solid or the maximum solute concentration in the Mg matrix. 36 We optimized the atomic structure of bulk materials and then constructed the surface slab model with respect to the growth orientations of the α-Mg dendrite.…”
Section: Resultsmentioning
confidence: 99%
“…36,37 The concentration of the additional elements for the magnesium alloys was chosen on the basis of their solubility in the solid or the maximum solute concentration in the Mg matrix. 36 We optimized the atomic structure of bulk materials and then constructed the surface slab model with respect to the growth orientations of the α-Mg dendrite. In terms of an n -layer surface slab model with respect to the { hkil } plane, the surface energy can be obtained via 30,33 where E slab n is the total energy per primitive slab unit cell, E bulk is the total energy per primitive bulk unit cell, S is the surface area per primitive slab unit cell, and the factor of 2 accounts for two equivalent surfaces of a particular slab model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[49][50][51] Increasing contents of Al and Zn have also been reported to change the growth direction in the nonbasal plane from 1123 to 2245 . [48] Apart from alloying elements, the solidification method and cooling rate were found to have a significant influence on dendrite morphology, but not growth orientation. [41,47,52] Specifically, Shuai et al showed that slower cooling rates (3 C min À1 ) were found to result in globular dendrite morphologies, while faster cooling (12 C min À1 ) revealed sixfold symmetry for Mg-15Sn.…”
Section: α-Mg Dendrite Formation and Evolutionmentioning
confidence: 94%
“…Specifically, a sixfold symmetry of α‐Mg dendrites in the basal plane was observed for Mg–9Al, [ 42,43 ] Mg–40Zn, [ 44 ] Mg–30Sn, Mg–30Gd, [ 45 ] Mg–30Sn, Mg–25Al, Mg–10Ba, Mg–20Y, [ 46 ] and Mg–15Sn. [ 47 ] The primary dendrite growth direction in most cases was 11 true 2 ¯ 0 , [ 48 ] while different authors identified either the 22 true 4 ¯ 5 [ 44 ] or 11 true 2 ¯ 3 [ 45,46 ] as second growth direction, with the difference being attributed to measurement uncertainty by some authors. [ 46 ]…”
Section: Alloy Developmentmentioning
confidence: 99%